Children and war in Africa: the crisis continues in Northern Uganda - Angucia, Margaret (International Journal on World Peace, 2009)
The use of children in warfare is per haps as old as humanity. Suggestions of children's involvement in warfare range from as far back as ancient Greece (Macmillan, 2009) to the twelfth century (Honwana, 2006). Skinner (1999) points out the 1212 French and Ger man children's crusade and the use of youth by Hider at the end of the Third Reich. The involvement of children of Colombia, Cambodia, Palestine, Afghanistan, Bosnia, Croatia and Her zegovina among others (Honwana, 2006; UNICEF, 2005; Skinner, 1999) in conflict are also public knowledge, thanks to the media.
Keywords: Children; War; Northern Uganda